Navigating the Landscape of Higher Engineering Education Coping with decades of accelerating change ahead - Kamp, Aldert (TU Delft Open, 2023)
Some times call for a change, some require consolidation. The question is: in which time do you live? Staring into the future doesn't help, focusing too much on the past neither. It requires 'reading the past to predict the future'. For that an open mind is needed, a critical assessing of the current and the past. For more than a decade, Ir. Aldert Kamp has done so. While in charge of the educational programmes of TU Delft's Aerospace Engineers, he constantly scanned the world for clues on how to educate young engineers. Aldert consistently made a plea for outward looking: "open the windows and look around in the world; let the world flow in". And so he did, travelling around, visiting the leading conferences and being a well-respected key note speaker, recognized by the great institutions like MIT. Aldert Kamp organised think tanks, free spirits to discuss the future of engineering education. He talked to the major industries trying to understand in what direction they were moving and what that meant for the education of the next generation (aeronautical) engineers. His ideas took shape more and more into the direction of real change. The current times are times of fast change, of greater uncertainty. Consolidation is no longer an option. Sure, engineers need engineering skills. But that will not suffice. Additional skills are needed and they cannot all be put in the heads and minds of each individual student. That made Aldert Kamp come up with various roles for different engineers. Roles that have one thing in common: they are connected to other roles and areas. Working in splendid isolation and then passing on the work to the next engineer is out. Team work, with multiple disciplines in each team, socially responsible engineering, entrepreneurial thinking, innovator roles, system thinkers and sustainability: those are the new ways of the world. In this book, Aldert has put together all the ideas, knowledge that he gained over the years. Read it! Even if you are not convinced that we are living in rapidly changing times. The timing of the book, now that the world is in turmoil due the corona virus couldn't be better. Changing times, that's what we are facing. And we have to find answers to cope with this. In this book you will find food for thought and inspiration from one of the current thought leaders in engineering education.